2014
DOI: 10.3390/toxins6102912
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Potential Toxin-Producing Cyanobacteria in an Oligo-Mesotrophic Lake in Baltic Lake District, Germany: An Ecological, Genetic and Toxicological Survey

Abstract: Massive developments of potentially toxic cyanobacteria in Lake Stechlin, an oligo-mesotrophic lake in the Baltic Lake District of Germany raised concerns about toxic contamination of these important ecosystems. Field samples in the phase of mass developments of cyanobacteria were used for genetic and toxicological analyses. Microcystins and microcystin genes were detected in field samples of the lake for the first time. However, the toxins were not produced by the dominant taxa (Dolichospermum circinale and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 65 publications
6
12
0
Order By: Relevance
“…was the only microcystin producer present. Those findings are in line with other studies, which found that the dominant microcystin producer is not necessarily the dominant cyanobacterial species in a water body ( Dadheech et al, 2014 ). Similar to our study, Lee et al (2015) identified low abundant Microcystis sp.…”
Section: Discussionsupporting
confidence: 93%
“…was the only microcystin producer present. Those findings are in line with other studies, which found that the dominant microcystin producer is not necessarily the dominant cyanobacterial species in a water body ( Dadheech et al, 2014 ). Similar to our study, Lee et al (2015) identified low abundant Microcystis sp.…”
Section: Discussionsupporting
confidence: 93%
“…The absence of Anatoxin-a genes in the studied lake is in agreement with previous screening for a toxin screening in the lake [77].…”
Section: Discussionsupporting
confidence: 90%
“…S4), while there were several taxa of equal abundance in summer including C. meneghiniana , Cyclostephanos, Chlamydomonas , Nitzschia, Coelastrum , Navicula , and Scenedesmus . Cyanobacteria, including Oscillatoria, Pseudanabaena , and Planktothrix sp., with the latter being a well‐known toxin producer in temperate lakes (Ernst et al ; Dadheech et al ), were present in low relative abundance. Community composition in summer was more diverse than in spring (Fig.…”
Section: Resultsmentioning
confidence: 99%